2016
DOI: 10.1016/j.cell.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the CUL3 Ubiquitin Ligase by a Calcium-Dependent Co-adaptor

Abstract: The ubiquitin ligase CUL3 is an essential regulator of neural crest specification whose aberrant activation has been linked to autism, schizophrenia, and hypertension. CUL3 exerts its roles by pairing with ∼90 distinct substrate adaptors, yet how the different CUL3-complexes are activated is poorly understood. Here, we show that CUL3 and its adaptor KLHL12 require two calcium-binding proteins, PEF1 and ALG2, for recognition of their substrate SEC31. PEF1 and ALG2 form a target-specific co-adaptor that translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
157
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 118 publications
(175 citation statements)
references
References 51 publications
14
157
3
1
Order By: Relevance
“…As with previous work, we noted in these data the small number of Sec31A-positive puncta evident in many of the images (Gorur et al 2017; Jin et al 2012; McGourty et al 2016). The motile structures observed (Gorur et al 2017) are not shown to undergo long-range transport.…”
Section: Flexibility Of the Copii Coat: The Case For Large Copii-depesupporting
confidence: 89%
See 4 more Smart Citations
“…As with previous work, we noted in these data the small number of Sec31A-positive puncta evident in many of the images (Gorur et al 2017; Jin et al 2012; McGourty et al 2016). The motile structures observed (Gorur et al 2017) are not shown to undergo long-range transport.…”
Section: Flexibility Of the Copii Coat: The Case For Large Copii-depesupporting
confidence: 89%
“…As with the earlier work, here a small number of large structures were seen in cells overexpressing KLHL12 that labelled for Sec31A, PEF1 and ALG-2 (McGourty et al 2016). This work also showed for the first time that these larger structures can be labelled with antibodies against procollagen and that depletion of either ALG-2 or PEF1 inhibited secretion of procollagen in HT1080 cells overexpressing type I procollagen (McGourty et al 2016). Then, in 2017, the Schekman group reported large, procollagen- and Sec31A-positive structures in KI6 cells (Gorur et al 2017).…”
Section: Flexibility Of the Copii Coat: The Case For Large Copii-depesupporting
confidence: 84%
See 3 more Smart Citations